Technology-Enhanced Course in English Theoretical Grammar and Phonetics at Tertiary Level - Jana Kuzmina; Zigrīda Vinčela (Baltic Journal of English Language, Literature and Culture)
The advancement of technologies and the recently forced lockdown by Covid-19 are bringing changes to the organisation of the learning process by accelerating the introduction of e-learning to create a learner-centred technology-based approach to English studies, thus stepping towards digital humanities. These trends initiated the institutional project Mobile and Desktop Software Integration in Bachelor and Master Study Programmes. The present study, using a questionnaire, elicits university students’ attitudes to the mobile applications and speech analysis software-based seminar activities in Moodle e-course in accordance with the blended learning model selected for the studies of theoretical grammar and phonetics. It is a cross-sectional, focused, and exploratory case study, comprising a description of factors, contributing to the problem of blended learning model selection. The yielded data demonstrate that students do not possess extensive prior experience with the use of software and mobile applications to study English grammar and phonetics. After completing seminar tasks, they favourably account for the integrated blended learning materials and consider that those facilitate their learning process.